The Effect of Buying Decisions on Mutiara City Housing in Banjarbendo Village, Sidoarjo Regency - Safa'at Safa'at; Noneng R Sukatmadiredja (ITB AAS INDONESIA, 2022)
The purpose of present research was to investigate the Effect of Location, Promotion, and Sociality on the Buying Decision of Mutiara City Housing in Banjarbendo Village, Sidoarjo Regency, either partially or simultaneously. This study uses a quantitative method with a population of 327 housing buyers, the sample using the Slovin formula for a sample of 77 respondents. Data analysis is classical assumption test, multiple linear regression, validity test, reliability test, and hypothesis test. Findings of present research can be seen that the statistical t value resulting from the influence of Location (X1) on Purchase Decisions (Y) is 4.419 with a significance value of 0.000. The significance value is lower than the significant alpha 5% or 0.05. It indicates that there is a significant effect of Location (X1) on Purchase Decisions (Y), the t-statistical value resulting from the effect of Promotion (X2) on Purchase Decisions (Y) is 0.361 with a significance value of 0.719. The significance value is higher than the significant alpha 5% or 0.05. It indicates that there is no significant effect of Promotion (X2) on Buying Decision (Y). The lower value of the t statistic resulting from the influence of Sociality (X3) on Buying Decision (Y) is 9.532 with a significance value of 0.000. The significance value is lower than the significant alpha 5% or 0.05. It indicates that there is a significant effect of Sociality (X3) on Purchase Decisions (Y). The results of the analysis of the simultaneous influence test resulted in a calculated F value of 114.001 with a probability of 0.000. Test results present the probability